Hydrothermal Fabrication of NiAl-LDH Coupled with Spirulina Hydrochar for Efficient Photodegradation of Methylene Blue - Ramadhan, Navinda; Komis, Komis; Sari, Novita; Normah, Normah (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
In this study, a Ni/Al layered double hydroxide (LDH) coupled with Spirulina-derived hydrochar was successfully synthesizedvia a microwave-assisted hydrothermal method for the photodegradation of methylene blue (MB) under visible light irradiation.The incorporation of hydrochar significantly modified the structural, surface, and optical properties of Ni/Al-LDH, resultingin enhanced photocatalytic performance. Characterization results confirmed the successful formation of the compositewith improved surface area and extended light absorption. Photodegradation experiments revealed that the Ni/Al-Spirulinacomposite exhibited superior performance compared to pristine Ni/Al-LDH, achieving higher degradation efficiency undervarious conditions. The enhanced activity was influenced by operational parameters such as pH, catalyst dosage, and initial dyeconcentration, with optimal performance observed under near-neutral conditions. The improved performance is attributed tothe synergistic effect between adsorption and photocatalysis, where hydrochar facilitates charge separation and promotes thegeneration of reactive oxygen species. Overall, this study demonstrates an effective strategy for developing biomass-based LDHcomposites as efficient and sustainable photocatalysts for wastewater treatment